Exercise Capacity, Ventilatory Response, and Gas Exchange in COPD Patients With Mild to Severe Obstruction Residing at High Altitude - Gonzalez-Garcia, Mauricio; Barrero, Margarita; Maldonado, Dario (Frontiers in Physiology, 2021)
Background: Exercise intolerance, desaturation and dyspnea are common features in patients with chronic obstructive pulmonary disease (COPD). At altitude, the barometric pressure decreases, and therefore the inspired oxygen pressure and the partial pressure of arterial oxygen (PaO2) also decrease in healthy subjects and even more in patients with COPD. Most of the studies evaluating ventilation and arterial blood gas (ABG) during exercise in COPD patients have been conducted at sea level and in small populations of people ascending to high altitudes. Our objective was to compare exercise capacity, gas exchange, ventilatory alterations and symptoms in COPD patients residents at the altitude of Bogota (2640m), of all degrees of severity. Methods: Measurement during a cardiopulmonary exercise test of oxygen consumption (VO2), minute ventilation (VE), tidal volume (VT), heart rate, ventilatory equivalents of CO2 (VE/VCO2), inspiratory capacity (IC), end-tidal carbon dioxide tension (PETCO2) and ABG. For the comparison of the variables between the control subjects and the patients according to the GOLD stages, the non-parametric Kruskal-Wallis test or the one-way ANOVA test were used. Results: 81 controls and 525 patients with COPD aged 67.5 ± 9.1 years were included. Compared with controls, COPD patients had lower VO2 and VE (p<0.001) and higher VE/VCO2 (p=0.001), A-aPO2, and VD/VT (p<0.001). In COPD patients, PaO2 and saturation decreased, and delta IC (p=0.004) and VT/IC increased (p=0.002). These alterations were also seen in mild COPD and progressed with increasing severity of the obstruction. Conclusion: The main findings of this study in COPD patients residing at high altitude, were a progressive decrease in exercise capacity, increased dyspnea, dynamic hyperinflation, restrictive mechanical constrains and gas exchange abnormalities during exercise, across GOLD stages 1 to 4. In patients with mild COPD, there were also lower exercise capacity and gas exchange alterations, with significant differences from controls. Compared with studies at sea level, due to the lower inspired oxygen pressure and the compensatory increase in ventilation, hypoxemia at rest and during exercise was more severe, PaCO2 and PETCO2 were lower and VE/VO2 higher.